Peningkatan keterampilan membaca pemahaman melalui model pembelajaran cooperative integrated reading and composition pada peserta didik kelas IV sekolah dasar - Brilliananda, Cindy Cindhana; Winarni, Retno; Sriyanto, Muhammad Ismail (Didaktika Dwija Indria, 2021)
This study aims to enhance reading comprehension skills through implementation of Cooperative Integrated Reading and Composition model. The subjects of the study are 26 students of the 4th grade in Pajang II elementary school, Laweyan, Surakarta. This research is Classroom Action Research consist of two cycles. Data collection is done by interviewing, observing, reading comprehension skills test, and document analysis. The data’s validity is done by using content validity, source triangulation, and technical triangulation. The data is analyzed using an interactive analysis model of Miles-Huberman and comparative descriptive model. The result of reading comprehension skills in pretest showed an average of 46,08. Then, in the first cycle, the average increase to 64,98 and become 83,5 on the second cycle. Thus, the conclusion that can be drawn regarding reading comprehension skills in 4th grade students of Pajang II elementary school academic year of 2019/2020 can be enhanced by applying Cooperative Integrated Reading and Composition model.l